A Systematic Literature Review: Implementation of IT Risk Management Using the NIST Framework in Education - Cika Alpi Nurpauji; Fahmi Idris Susanto; Muhammad Firas Hisyam; Muhamad Azmi; Ucu Nugraha (Jurnal Sistem Informasi dan Teknologi Informasi, 2025)
The rapid advancement of information technology (IT) has significantly transformed various industries, including education, through the implementation of information systems that streamline student admissions, pedagogy, and institutional administration. However, this digital evolution introduces critical data security risks. Effective IT risk management is therefore essential to safeguard sensitive data and prevent operational disruptions within educational institutions. One of the most prominent frameworks for this purpose is NIST Special Publication 800-30, which provides systematic guidance for identifying and assessing IT-related risks. The NIST framework assists educational institutions in identifying potential threats and vulnerabilities while establishing robust mitigation strategies. While the framework possesses immense potential to elevate IT risk awareness, its implementation in the education sector remains hindered by resource constraints, varying levels of IT literacy, and regulatory complexities. This research employs the Systematic Literature Review (SLR) method to analyze the implementation of the NIST framework in managing IT risks within the education sector. This methodology enables the identification and evaluation of relevant research findings regarding both the successes and challenges associated with the framework's adoption. Through a comprehensive literature analysis, this study offers strategic insights and recommendations to enhance the effectiveness of the NIST framework within technology-driven educational environments.